A Causality Study of Tinea Pedis Incidence in Scavengers at the Final Disposal Site (TPA) of Jatibarang Semarang in 2018 - Nilawati, Ida; Wijayanti, Yuni; Soesanto, Soesanto (Public Health Perspective Journal, 2021)
Tinea Pedis is a fungal infection that usually begins between the toes. It commonly occurs in people whose feet have become very sweaty while confined within tightfitting shoes. It often attacks adults who work in wet places such as washers, farmers or people who have to wear closed shoes every day, such as scavengers. The purpose of this study was to examine the causality of the incidence of Tinea pedis in scavengers at the Final Disposal Site (TPA) of Jatibarang, Semarang in 2018. This study was done using a type of quantitative research supported by qualitative data obtained from interviews, with a cross sectional approach. The sample used in this study were 78 respondents obtained by using simple random sampling technique. The data collection techniques were done by using interview, observation, and documentation (diagnostic report sheet of a dermatologist). The data analysis in this study was done using Descriptive Statistics, Chi Square and Multiple Logistics Regression tests. The results showed that there was an effect of changing socks used for work (p=0.000), the practice of washing and drying feet after work (p=0.000), the practice of washing shoes after being worn to work (p=0.000), individual characteristics (age (p=0.031), gender (p=0.046), education (p=0.024) and working periodÂ  (p=0.020) on the incidence of Tinea pedis among scavengers at the Final Disposal Site (TPA) Jatibarang, Semarang in 2018. The results of the logistic regression showed that the most dominant factors for causing the incidence of Tinea pedis on scavengers at the Final Disposal Site (TPA) Jatibarang, Semarang in 2018 is the practice of washing shoes after being used to work with an adjusted OR or Exp (B) = 45.179. It is expected that the results of this study able to increase the knowledge of scavengers about the risks of work, especially skin disease of Tinea pedis.